Multi-Function RF Seeker Based on 3D Phased Array - Kocjancic, Leon (Cranfield University, 2017)
3MT presentation at the 2016 Defence and Security Doctoral Symposium.Current RF seekers in use today have mechanical steerable antennas. In order to reduce the cost of the mechanical system and to significantly improve the performance of the missile seeker, the electrically controlled 3D antenna array is proposed. Given solution will result in a much more robust antenna which will be capable of steering much faster and more accurately than existing solutions. Furthermore, the proposed antenna will provide an increased coverage and dwell time as a result of flexible beam steering. Additional degrees of freedom will allow it to carry out multiple tasks.The main aim of proposed PhD is to investigate theoretical background and realization of multiple beams that will conduct different tasks, such as radio-altimetry, target seeking, proximity activation and radar imaging. By using 3D antenna as a co-located multiple-input multiple-output system and by using suitable orthogonal waveforms the novel seeker will be capable of generating multiple beams.
Keywords: 'DSDS16'; 'DSDS16 3MT'; 'MIMO radar waveforms'; 'Orthogonality'; 'RF seekers'; 'Antennas and Propagation'